ANALISIS PERTUMBUHAN EKONOMI DAN STUDI SEKTOR UNGGULAN DI KABUPATEN/KOTA SE-JAWA TENGAH - Atmanti, Hastarini Dwi (PRESTASI, 2010)
Economic growth is an indicator of economic achievement, espescially for economics. This indicator is important for region because can be used for evaluation of development achievement and for basis of planning and policy for the future. In the development procces, Province Central Java divide its region into three of parts which is called by Badan Koordinasi Pembangunan Lintas Kabupaten/kota (Bakorlin).Keyword: growth, development, Central Java, Bakorlin